Severe breakthrough COVID-19 with a heavily mutated variant in a multiple myeloma patient 10 weeks after vaccination. (January 2022) - Stampfer, Samuel D.; Goldwater, Marissa-Skye; Bujarski, Sean; Regidor, Bernard; Zhang, Wenjuan; Feinstein, Aaron J.; Swift, Regina; Eshaghian, Shahrooz; Vail, Eric; Berenson, James R.
Highlights: Multiple myeloma (MM) patients develop inconsistent responses to COVID-19 vaccination. One developed severe COVID-19 just 10 weeks after his second dose of mRNA-1273. Anti-spike IgG was 608 IU/mL 2 weeks post-vaccine but dropped to 126 IU/mL by week 8. Vaccination was partially protective as unvaccinated infected coworkers fared worse. Sequencing revealed a heavily-mutated B.1.628 variant with N440K and E484Q in spike. Abstract: Background: Patients with multiple myeloma have unpredictable responses to vaccination for COVID-19. Anti-spike antibody levels can determine which patients develop antibodies at levels similar to healthy controls, and are a known correlate of protection. Case report: A multiple myeloma patient developed protective anti-spike antibodies after vaccination (608 IU/mL), but nonetheless developed severe breakthrough COVID-19 just 10 weeks following his second vaccination with mRNA-1273. Results: Sequencing of the viral isolate revealed an extensively mutated variant with 10 spike protein mutations, including E484Q and N440K. Serology testing showed a dramatic decline in anti-spike antibodies immediately prior to virus exposure. Conclusions: Multiple myeloma patients who do develop detectable antibody responses to vaccination may be at increased risk for breakthrough infections due to rapid decline in antibody levels. Viral variants with immune escape mutations such as N440K, also seen independently in the SARS-CoV-2 Omicron variant (B.1.1.529) and in viral passaging experiments, likely require a higher level of anti-spike antibodies to prevent severe COVID-19.